Kompetensi emosi pada remaja - Novie Triana Wijayanti (Psychological Journal: Science and Practice, 2021)
Adolescents need the skills to express, understand and regulate emotions based on personality to face mood disorders or anxiety and internalization problems, the risk of maladaptive behavior and involvement in aggressive behavior, these skills are called emotional competence. Emotional competence is inﬂuenced by self-compassion to make individuals adapt more quickly, can develop sensitivity to suffering and understand how to treat themselves, so that individuals can respond to the pressure that comes with proper identiﬁcation and understanding of emotions, then regulate and express emotions as a form of emotional competence. The purpose of this study is to prove that the relationship between self compassion and emotional competence can be mediated by social support. This study was conducted on 222 adolescents from the age range of 12-18 years who were determined from several schools. This research uses a correlational quantitative approach which is measured using Self Compassion scales, Social Provision Scale and Personal emotional competence. Data were analyzed using modiation analysis regression. The ﬁndings of this study are that there is a mediating effect of social support on the relationship of self-compassion with emotional competence, which means that social support can be a mediator between the relationship of selfcompassion and emotional competence.